SWOT: Bisnis UMKM pada Fakultas Ekonomi dan Bisnis Universitas Khairun - Septy Indra Santoso; Fahdia Santoso; Roswiyanti Roswiyanti; Dyan Fauziah Suryadi; Andi Gunawan (Tangible Journal, 2026)
This study aims to analyze the condition of MSMEs using a SWOT (Strengths, Weaknesses, Opportunities, Threats) approach to identify internal and external factors that influence business sustainability. The study used a descriptive qualitative method with data collection techniques through direct interviews with culinary MSME actors in the Faculty of Economics and Business, Khairun University with three informants. The results of the study indicate that the main strengths of MSMEs lie in affordable prices, strategic business locations, product variations that suit consumer needs, and fast service. The weaknesses faced include limited capital, disruption to clean water access, limited business space, a decrease in the number of consumers during academic holidays, and inadequate supporting facilities.